Prenylation of Flavonoids by Using a Dimethylallyltryptophan Synthase, 7-DMATS, from Aspergillus fumigatus - Yu, Xia; Li, Shu-Ming (Chembiochem : a European journal of chemical biology, 2011)
Production of typical plant metabolites by a fungal enzyme: Fungal prenyltransferases of the DMATS superfamily are mainly involved in the biosynthesis of prenylated indole alkaloids, but also catalyze the prenylation of tyrosine and naphthalene derivatives. In this study, nine prenylated flavonoids were produced by using the recombinant dimethylallyltryptophan synthase 7‐DMATS from Aspergillus fumigatus.